(untitled) (Research, Society and Development, 2022)
With the discovery of the new coronavirus in 2019, in china the world was faced with the dissemination of false news, as fake news, which led to various misinformation and misinformation of the population in relation to COVID-19 and its treatment. this article sought to make a correlation or bring up a discussion about the dissemination of false news and the Scientific and Technological Literacy of the population, seeking to address the issue as a way to reduce the credibility of these untrue news, from the literate citizen. scientifically and technologically, giving it the insight so that it can look for reliable sources to confirm or even refute information based on reliable sources. imagining that the ACT, I can provide the person with a way to solve and participate in the resolution of problems caused by science and technology, because he will know how to pricire reliable sources to support his response to the problem, and false news emerges as a problematic that needs resolution. In this article, an attempt was also made to report on the topics covered, and for this, an integrative literature review was carried out with the main focus on the relationship of citizen education.